2013
DOI: 10.1371/journal.pone.0071326
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Does Not Produce Relief of Neuropathic Pain in Mice Lacking the β-Common Receptor (CD131)

Abstract: Neuropathic pain (NP) is a debilitating condition associated with traumatic, metabolic, autoimmune and neurological etiologies. Although the triggers for NP are diverse, there are common underlying pathways, including activation of immune cells in the spinal cord and up-regulation of the N-methyl-D-aspartate receptor (NMDAR). Ketamine, a well-known NDMAR antagonist, reduces neuropathic pain in a sustained manner. Recent study has shown that the novel 11-amino acid peptide erythropoietin derivative ARA290 produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Here we describe for the first time the physical interaction between EpoR and βcR in mouse skeletal muscle by immunoprecipitation assays, showing that the pharmacological target of pHBSP, the EpoR/βcR complex, was expressed in the skeletal muscle of both control and HFHS‐fed mice. pHBSP is known to bind to the EpoR/βcR complex (Brines and Cerami, 2008; 2012; Bohr et al ., ) and no effect of pHBSP in mice lacking the βcR has been reported (Swartjes et al ., 2011; 2013). However, further studies on the effects of pHBSP in βcR knockout mice given a HFHS diet are necessary to confirm that the observed beneficial effects of this peptide are indeed due to activation of the EpoR/βcR complex.…”
Section: Discussionmentioning
confidence: 99%
“…Here we describe for the first time the physical interaction between EpoR and βcR in mouse skeletal muscle by immunoprecipitation assays, showing that the pharmacological target of pHBSP, the EpoR/βcR complex, was expressed in the skeletal muscle of both control and HFHS‐fed mice. pHBSP is known to bind to the EpoR/βcR complex (Brines and Cerami, 2008; 2012; Bohr et al ., ) and no effect of pHBSP in mice lacking the βcR has been reported (Swartjes et al ., 2011; 2013). However, further studies on the effects of pHBSP in βcR knockout mice given a HFHS diet are necessary to confirm that the observed beneficial effects of this peptide are indeed due to activation of the EpoR/βcR complex.…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical models of neuropathy, ARA 290 has been shown to prevent and improve peripheral neuropathic pain, an action that requires the innate repair receptor (25). In these effects, ARA 290 is not acting as an analgesic agent (26), but rather reduces the underlying inflammation (27) and stimulates nerve fiber regrowth from damaged axons. Recent studies of patients with sarcoidosis and SFN have shown that ARA 290 reduces neuropathic symptoms in conjunction with an increase of small nerve fibers as assessed by changes in the density of corneal nerve fibers (19).…”
Section: Introductionmentioning
confidence: 99%
“…A thorough review of our recording and management of side effects is in process. Identifying the patients who may benefit as ketamine responders is ongoing with clinical trials and research that suggest there are certain individuals and etiology subtypes whose NP may or may not respond to ketamine [5]. We find that CRPS patients with refractory pain have demonstrated the greatest benefit from ketamine via IV infusions.…”
Section: Discussionmentioning
confidence: 85%
“…Mechanisms underlying NP include altered gene expression, changes in gene regulation within the CNS, changes in ion channels that lead to ectopic activity, and synaptic facilitation of the neural axis producing central amplification [3]. The activation and upregulation of dorsal horn excitatory glutamatergic N-methyl-D-aspartate (NMDA) receptors is believed to play a central role in NP, allodynia, and hyperalgesia [4,5].…”
Section: Introductionmentioning
confidence: 99%